Pengaruh Modal Usaha, Lokasi Usaha, dan Lama Usaha Terhadap Pendapatan UMKM - Putri, Berliana; Fietroh, Muhammad Nur (TIN: Terapan Informatika Nusantara, 2025)
This study aims to analyze the influence of business capital, business location, and business duration on the income of Micro, Small, and Medium Enterprises (MSMEs) in Sumbawa Regency. Using a quantitative approach with a causal-explanatory design, this study applies multiple linear regression analysis to test the relationship between variables. A total of 100 MSME respondents were selected through proportional random sampling technique from a population of 1632 business units. Data were collected using a structured questionnaire and have been tested for validity through the classical assumption test. The results showed that business capital (t = 3.689; p < 0.05), business location (t = 4.572; p < 0.05), and business duration (t = 4.045; p < 0.05) each have a positive and significant effect on MSME income. Among the three, business location is the most dominant factor with the highest beta coefficient (β = 0.318), indicating that strategic geographic location has a stronger influence on increasing income compared to capital (β = 0.256) and business duration (β = 0.287). The implication of this finding suggests that external factors such as accessibility and market reach can be more decisive in determining business success. This study fills a gap in the literature by providing local context-based empirical evidence regarding the factors that influence MSME income, particularly in non-metropolitan areas such as Sumbawa. The results provide valuable recommendations for local governments, financial institutions, and MSME actors in designing inclusive economic development strategies.